Edukasi Pentingnya Penerapan Kesehatan dan Keselamatan Kerja Pada Masyarakat Pengelola Usaha Jasa Pelayanan Reparasi Kendaraan Bermotor di Desa Air Napal, Bengkulu Tengah - Yayan Kurniawan; Sutri Yani (Bengkulu Institute, 2023)
Introduction The automotive industry is currently a sector that is a mainstay for the people of Indonesia, the Ministry of Industry (2021) notes that there are at least more than 26 companies engaged in the four-wheeled and two-wheeled vehicle industry. This increase encouraged the company to open branches massively. The application of Occupational Health and Safety culture will be very beneficial for both the owner and the workers. Until now, every company that has been standardized has implemented the principles of Occupational Health and Safety. This community service activity was carried out at the Ferry Motor Workshop, Air Napal Village, Central Bengkulu. The purpose of this activity is to provide an understanding as well as the implementation of Occupational Health and Safety culture in the Ferry Motor Workshop. The Method used is to provide education to four participants. Providing education is carried out through five (stages), namely assessing participants' knowledge about Occupational Health and Safety, Providing education about the dangers of ignoring Occupational Health and Safety, Demonstrating how to use PPE, Providing opportunities for participants to use, and evaluating the results of the education. The results found that by providing education related to the importance of implementing an Occupational Health and Safety culture it can have an impact on public knowledge and awareness so that behavior is in accordance with Occupational Health and Safety principles. Keywords: Occupational Health and Safety Education, Motor Vehicle Repair Services